Physiology of the menstrual cycle. - García La Madrid, Martín (2015)
It is known today that the production and release of pituitary gonadotropins are governed by hypothalamic centers that have the ability to react to estrogen and progesterone concentrations in circulation, to modify the regulation practicing in the pituitary. The follicle stimulating hormone (FSH), luteinizing hormone (LH), also called stimulating hormone interstitial cells (ICSH), and luteotropic hormone (LTH) are hormones produced by the anterior pituitary that relate specifically to the regulation ovulation.